Att gestalta undergången: En studie av hur P3 Dystopia och dess lyssnare ser på klimatförändringarna - Oskarsson,Magnus (2025)
The future in a world of climate change is yet to be written. In this study I explore how climate change and its consequences can be framed in dystopian and apocalyptic visions of the future. This is done by studying a Swedish radio podcast called P3 Dystopia. I also research what views the listeners of the podcast express regarding climate change and through which discourses these views can be understood. This is achieved by analyzing comments in a Facebook group where the podcast is discussed. Here I show that the podcast defines climate change as a problem that will have, and already has, severe effects on society because of greenhouse gas emissions. A moral judgment is that the actions we make today will decide if future generations will inherit a livable planet. The remedies are adapting to climate change, but also to engage in mitigating it. The listeners of the podcast react to this in many ways, including anxiety, grief, resignation, and indifference. Some encourage action and advocate for activism. The reactions can be understood through environmental discourses of survivalism, sustainable development, and radicalism. The study shows that dystopian and apocalyptic framing can be used to open up the future by using the apocalypse as a metaphor to “think the unthinkable”. However, it requires visions to be based upon a combination of natural sciences and knowledge of society. This type of dystopian visioning could be used in the academic environmental field as well as by the media to encourage a democratic dialogue regarding desired futures. Still there is no guarantee that they will lead to dedication rather than climate despair.
Keywords: climate change; future studies; framing; apocalypse; podcasts